PEDAGOGICAL TECHNOLOGIES IN EDUCATIONAL PROCESS OF HIGHER SCHOOL - Elena A. Avdeeva; Irina A. Drozdova (Высшее образование в России)
The article highlights new educational technologies applicable in higher school educational process. Today the universities face challenge to achieve high-quality educational outcomes that meet the standard, and to provide the necessary level of motivation, health and development of students. To improve the quality of education and to develop students' competencies stated in the standard it is expedient to use modern educational technologies such as technologies for the revitalization and intensification of students' activities on the basis of schematic and symbolic models, modular system, enlarged didactic units, new information technology training, mind-management, etc. These technologies allow to analyze any volume of information quickly and to make thorough decisions to achieve your goal, to communicate efficiently, and to present the result simply and clearly.